2018
DOI: 10.2497/jjspm.65.659
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Internal Structure of Ceramics and Slurry by Optical Coherence Tomography

Abstract: Optical coherence tomography (OCT) is an observation technique utilizing optical interferometry. Images of the internal structure of opaque materials can be obtained dynamically and three-dimensionally in a few seconds. In this work, the internal structures of ceramic sintered body and slurry was observed by OCT. In the case of Al 2 O 3 ceramics, an artificially induced spherical defect having smaller than 50 µm in diameter which lies 700 μm below the top surface was observed successfully. Furthermore, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Finally, a three-dimensional image (termed C-scan) is also obtained by two-dimensional scanning of the light nondestructively. 18) The depth at which information can be obtained with A-scan is determined by the refractive index of the material and the laser's ability. When Al 2 O 3 is observed with commercially available OCT, the typical coherence length, namely observable depth, is 2.3 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a three-dimensional image (termed C-scan) is also obtained by two-dimensional scanning of the light nondestructively. 18) The depth at which information can be obtained with A-scan is determined by the refractive index of the material and the laser's ability. When Al 2 O 3 is observed with commercially available OCT, the typical coherence length, namely observable depth, is 2.3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that spherical artificial pores with dimensions of 50¯m at a depth of 700¯m were observed from the surface in Al 2 O 3 . 18) The prediction of strength based on defect analysis in ceramics using OCT is not performed to date. However, OCT is a useful tool to observe defects in ceramics because OCT can obtain high-speed, high-resolution, non-destructive, and threedimensional observations.…”
Section: Introductionmentioning
confidence: 99%
“…In the infrared transmission image, bright spots with sizes of several tens of micrometers were also observed. According to our previous reports, the bright pairs in the OCT images originate from the reflections at the upper and lower surfaces of the pore 23,24 . Although SEM observations of the same positions are not available in this study, it is suggested that there are large pores in the Al 2 O 3 ceramics that grew during sintering.…”
Section: Resultsmentioning
confidence: 56%
“…We have been employing optical coherence tomography (OCT) to observe the internal structure of ceramics 23,24 . OCT is a nondestructive observation method based on optical interferometry 25–27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation